Teacher Candidates as LGBTQ and Social Justice Advocates through Curricular Action - Tompkins, Joanne; Kearns, Laura-Lee; Mitton-Kükner, Jennifer (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2017)
Critical challenges facing teacher educators at faculties of education is how to prepare teacher candidates to see schools situated in larger social contexts and support their ongoing learning as social justice advocates. Anti-oppressive work that challenges the marginalization of Lesbian, Gay, Bi-sexual, Transgender, Two-Spirited, Queering and/or Questioning (LGBTQ) youth is critical to this work. The purpose of this paper is twofold, first to understand the impact of the Positive Space program on teacher candidates’ reasons and abilities to act as allies and social justice advocates. Second, we explore the process of teacher candidates becoming knowledgeable, empowered, and action-oriented for, with, and as LGBTQ community members and the ways they challenge heteronormativity and the gender binary through the formal and informal curriculum.